Women's ecological oral histories of recycling and development in coastal Yucatán. Issue 4 (2nd April 2016) - Hanson, Anne-Marie S.
Abstract : This article addresses the formation of the Chen Kole 'Lob women's recycling cooperative and its relationship to urbanization, plastics consumption, and the exclusionary spaces of conservation-as-development in coastal Yucatán, Mexico. Increasing amounts of plastic containers and other nonorganic garbage contaminate backyards, protected wetlands and marine areas, and individual homes located in low-lying floodable areas. However, in this region, the majority of sponsored economic development programs are directed at managing men's activities in sustainable fishing and ecotourism within natural protected areas. Both women's work and urban issues such as recycling and waste management have frequently been excluded from state policies and development practice. I draw from oral histories of women's experience in the home, in conservation space, and as participants in grassroots plastics recycling to underscore what motivated women to become involved in recycling and garbage cleanup, and how women came to be considered local professionals who maintain clean spaces. These histories underscore the links between gendered work, urban practices, and conservation-as-development, and how women's urban recycling work affects social differences and ecological decline within vulnerable coastal areas.